2016
DOI: 10.1111/pace.12812
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes Following Transvenous Lead Extraction

Abstract: Long-term mortality following TLE is high, particularly in those with systemic infection, procedural complications, advanced age, and renal impairment. Retained fragments are a risk factor for CDI post extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 15 publications
7
65
0
Order By: Relevance
“…However, implant-related complications associated with transvenous lead placement, including pneumothorax, cardiac perforation and tamponade, occur in 3%,1 while long-term complications such as infection, endocarditis and lead failure occur in up to 20% of TV-ICD leads at 10 years 2. Extraction of transvenous leads carries significant morbidity and mortality 3. The subcutaneous implantable cardioverter defibrillator (S-ICD) system is entirely extravascular, offering the potential to address these shortcomings 4…”
Section: Introductionmentioning
confidence: 99%
“…However, implant-related complications associated with transvenous lead placement, including pneumothorax, cardiac perforation and tamponade, occur in 3%,1 while long-term complications such as infection, endocarditis and lead failure occur in up to 20% of TV-ICD leads at 10 years 2. Extraction of transvenous leads carries significant morbidity and mortality 3. The subcutaneous implantable cardioverter defibrillator (S-ICD) system is entirely extravascular, offering the potential to address these shortcomings 4…”
Section: Introductionmentioning
confidence: 99%
“…31 System extraction is associated with a small risk of major complications, particularly vascular lacerations causing haemothorax and death. 32,70,[79][80][81][82] Extraction-related mortality rates are 0.1-0.8 % in large experienced centres. 70,83 In one large, single-centre study, including more than 5,000 lead extractions, 43 % of which were due to infection, risk of major complications was 1.8 %, and minor complications 3.6 %.…”
Section: Outcomes Of Cardiac Implantable Electronic Device Infectionmentioning
confidence: 99%
“…10,68,69 In a recent study, it was found that the rate of CIED infection after CIED extraction was higher in patients with incomplete lead removal, 13.5 % versus 3.0 %. 70 In addition, mortality appears higher without complete removal. [71][72][73] One study indicated a threefold higher mortality without system removal.…”
Section: Outcomes Of Cardiac Implantable Electronic Device Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7] Anticipating complications before they happen is the watchword in lead extractions. [4][5][6][7] Anticipating complications before they happen is the watchword in lead extractions.…”
Section: Defining the Problemmentioning
confidence: 99%